Building Inclusive Payment Ecosystems in Tanzania and Ghana - Mattern, Max; McKay, Claudia (World Bank, Washington, DC, 2018)
Over the past decade, financial services for the poor have undergone a dramatic transformation. For years, financial institutions like banks and microfinance institutions (MFIs) struggled to sustainably serve the world’s poor. But advances in technology have led to innovative business models, and with them, new opportunities for expanding the reach of financial services. At the heart of this financial transformation is the rise of digital payments services through which nearly any individual or business can send or receive money in real time for almost any purpose and from nearly anywhere in the country, an inclusive payment ecosystem. Overall, the main message that emerges from a review of both country experiences is that interoperability is important, but it is best pursued in mature markets. Engagement with industry is important, and regulators should be cautious when mandating interoperability so as not to hinder early investment. Stakeholders need to focus on governance and business rules, as was the case in the year-long negotiations between providers in Tanzania, and not just the technical implementation, which is currently the overwhelming focus in Ghana. As both markets continue to mature, it will be important to monitor the Tanzanian and Ghanaian experiences in the years to come to fully understand the impact of interoperability on DFS.